A Comprehensive Guide to the MAGE Family of Ubiquitin Ligases. Issue 8 (21st April 2017) - Lee, Anna K.; Potts, Patrick Ryan
Abstract: Melanoma antigen (MAGE) genes are conserved in all eukaryotes and encode for proteins sharing a common MAGE homology domain. Although only a single MAGE gene exists in lower eukaryotes, the MAGE family rapidly expanded in eutherians and consists of more than 50 highly conserved genes in humans. A subset of MAGEs initially garnered interest as cancer biomarkers and immunotherapeutic targets due to their antigenic properties and unique expression pattern that is primary restricted to germ cells and aberrantly reactivated in various cancers. However, further investigation revealed that MAGEs not only drive tumorigenesis but also regulate pathways essential for diverse cellular and developmental processes. Therefore, MAGEs are implicated in a broad range of diseases including neurodevelopmental, renal, and lung disorders, and cancer. Recent biochemical and biophysical studies indicate that MAGEs assemble with E3 RING ubiquitin ligases to form MAGE-RING ligases (MRLs) and act as regulators of ubiquitination by modulating ligase activity, substrate specification, and subcellular localization. Here, we present a comprehensive guide to MAGEs highlighting the molecular mechanisms of MRLs and their physiological roles in germ cell and neural development, oncogenic functions in cancer, and potential as therapeutic targets in disease. Graphical Abstract: Highlights: The MAGE family is evolutionarily conserved and consists of > 50 genes in humans. MAGE proteins function in MRL complexes to direct ubiquitination. Type I MAGEs are expressed in reproductive tissues and function in germ cell development. When aberrantly expressed, type I MAGEs function as oncogenes to drive tumorigenesis. Type II MAGEs are broadly expressed, and disruption results in neurodevelopmental defects.